A case report of genetic prion disease with two different PRNP variants. Issue 3 (17th January 2020) - Piazza, Megan; Prior, Thomas W.; Khalsa, Prabhjot S.; Appleby, Brian
Abstract: Background: Prion diseases are a group of lethal neurodegenerative conditions that occur when the normal, cellular form of the prion protein (PrP C ) is converted into an abnormal, scrapie, form of the protein (PrP Sc ). Disease may be caused by genetic, infectious, or sporadic etiologies. The genetic form of prion disease comprises 10%–15% of all cases. Prion disease is typically inherited in an autosomal dominant manner. The low incidence of disease makes it highly unlikely that a patient would have two different pathogenic variants. However, we recently identified a case in which the patient did have two pathogenic PRNP variants and presented with an atypical phenotype. Methods: The patient was evaluated at the Washington Hospital Healthcare System in Fremont, CA. The clinical information for this case report was obtained retrospectively. Variants in the PRNP were identified by polymerase chain reaction (PCR) amplification of exon two of the gene followed by bi‐directional sequence analysis. To determine the phase of the identified variants, a restriction enzyme digestion was utilized, followed by sequence analysis of the products. Cerebral spinal fluid (CSF) was analyzed for surrogate markers of prion disease, 14–3–3 and Tau proteins. CSF real‐time quaking‐induced conversion (RT‐QuIC) assays were also performed. Results: The patient was a compound heterozygote for the well‐characterized c.628G>A (p.Val210Ile) variant and the rare octapeptide deletion of two repeats [c.202_249del48 (p.P68_Q83del)]. Clinically, the patient presented with an early onset demyelinating peripheral neuropathy, followed by later onset cognitive symptoms. Conclusion: This presentation is reminiscent of prion protein knockout mice whose predominate symptom, due to complete loss of PrP, was late‐onset peripheral neuropathy. To our knowledge this is the first case reported of a patient with prion disease who had two different pathogenic variants in PRNP . Abstract : Genetic prion disease is typically inherited in an autosomal dominant manner and the low incidence of disease makes it highly unlikely that a patient would inherit two different pathogenic mutations, however, we recently identified a case in which the patient did indeed inherit two pathogenic PRNP variants and presented with an atypical phenotype. The well‐characterized c.628G>A (p.V210I) variant and the rare octapeptide deletion of two repeats [c.202_249del48 (p.P68_Q83del)] was identified in the patient. To our knowledge this is the first case of a patient with prion disease who has two different variants in PRNP.